Manganese‐Catalyzed C−H Alkynylation: Expedient Peptide Synthesis and Modification. Issue 12 (9th February 2017) - Ruan, Zhixiong; Sauermann, Nicolas; Manoni, Elisabetta; Ackermann, Lutz
Abstract: Manganese(I)‐catalyzed C−H alkynylations with organic halides occurred with unparalleled substrate scope, and thus enabled step‐economical C−H functionalizations with silyl, aryl, alkenyl, and alkyl haloalkynes. The versatility of the manganese(I) catalysis manifold enabled C−H couplings with haloalkynes featuring, among others, fluorescent labels, steroids, and amino acids, thereby setting the stage for peptide ligation as well as the efficient molecular assembly of acyclic and cyclic peptides. A plausible catalytic cycle was proposed. Abstract : In with Mn : The versatile title reaction sets the stage for fluorescence labelling and ligation of structurally complex peptides by synergistic catalysis under racemization‐free conditions. A plausible catalytic cycle is proposed.